Growth of Eremanthus erythropappus (DC.) MacLeish in Different Planting Spacings - Kalill José Viana da Páscoa (Floresta e Ambiente, 2019)
ABSTRACT This study aimed to evaluate the growth of Eremanthus erythropappus (DC.) MacLeish submitted to different planting spacing and growth modelling based on the diameter and crown area projection, as well as to identify the best management strategy to be applied to control the competition, period and intensity of thinning. The evaluated planting spacings were: 1.5 × 1.5 m; 1.5 × 2.0 m; 1.5 × 2.5 m and 1.5 × 3.0 m. Diametric growth modelling in function of the age and crown area projection according to the mixed models methodology was efficient and the individual tree modelling allowed for defining a correct thinning prescription for tree plantations in relation to the percentage of removal needed at each spacing, thus permitting the trees to grow free from competition and produce trees with larger diameters.